Triatoma costalimai naturally infected by trypanosoma cruzi: A public health concern - Teves, Simone Caldas (2019)
The rupestrian Triatoma costalimai species has been found infected by Trypanosoma cruzi in wild, peridomicile, and intradomicile environments in the municipality of Aurora do Tocantins, Tocantins, Brazil. Proximity between rock outcrops increases the risk of vector transmission of Chagas disease via this species. This work describes a focus of colonization by T. costalimai specimens infected by T. cruzi in rock outcrops located in an urban area in this municipality. Parasitological examination of feces from the collected specimens, axenic cultivation of T. cruzi–positive samples, and genetic characterization of the isolates were performed. Nymph and adult specimens were collected with a high infection prevalence (64.5%) for T. cruzi discrete type unit (DTU I). Participation of the T. costalimai species in the wild cycle of T. cruzi in rock outcrops located in an urban area demonstrates the need for entomological surveillance and control of vector transmission of Chagas disease in the municipality of Aurora do Tocantins, Tocantins.